The Timing of Entry into New Markets - Debra J. Aron (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1991)
Under what circumstances will a successful incumbent in a related market be the first to enter a new market? We present a model in which the order of entry into new markets has long run effects on the firms' profits. We assume that a firm that is successfully producing in a related market has valuable information about the demand in the new market. By his choice of location in product space in the new market the incumbent reveals information about the demand to the potential entrant. Thus, the incumbent would like to enter after the newcomer in order to prevent the rival from free riding on his proprietary information; however, the rival would also like to enter second so that he can benefit from the other's information. When both firms want to enter last, the order of entry is modeled as a timing game in continuous time. Using a refinement of Nash equilibrium known as "risk-dominance" we show that when the informational advantage of the incumbent is very great, his implicit threat to wait out his rival is less powerful than the equivalent threat by the potential entrant, and the incumbent will enter first. On the other hand, the incumbent's lower incentive to enter the new market due to the "cannibalization" effect of entering a related market is a weapon that the incumbent can use to "force" the rival to enter first, in equilibrium. We also find that incumbent entrants into new markets are more likely to succeed in the new market, in equilibrium, than are newcomers, regardless of order of entry. On the other hand, looking cross sectionally across markets, incumbents are more likely to succeed when they are early rather than late entrants, but newcomers are more likely to succeed when they are late entrants than early.
Keywords: 330